Understanding Synthesis–Structure–Performance Correlations of Nanoarchitectured Activated Carbons for Electrochemical Applications and Carbon Capture - Zhang, Songtao; Zheng, Mingbo; Tang, Yijian; Zang, Rui; Zhang, Xinyu; Huang, Xiang; Chen, Yong; Yamauchi, Yusuke; Kaskel, Stefan; Pang, Huan (Advanced Functional Materials, 2022)
Activated carbons are one of the most important classes of high-surface-area porous materials. Owing to their unique structure, low price, and large-scale production technology, these porous carbons have been traditionally used as sorbents for eliminating contamination. In the past decade, many innovations have been seen in the synthesis, structure, applications, and theoretical and experimental methods. Herein, a comprehensive review of the up-to-date progress of activated carbons is presented from the viewpoint of synthetic chemistry and materials science. First, the critical textural properties are discussed, with special emphasis on the porous texture, heteroatom doping, surface functional groups, and partial graphitization. Next, the advanced synthetic strategies of activated carbons are summarized. Special attention is given to the reaction mechanism between activating agents and carbon sources, as well as the design of controlled forms and morphology. Then, their applicability in various emerging fields is covered, including supercapacitors, capacitive deionization, batteries, electrocatalysis, and carbon capture. In particular, this review highlights the potential synthesis–structure–property correlations of these porous materials. Finally, we present the future challenges and outlook for their success in energy and environmental science.
CRIS-Team Scopus Importer:2023-03-20
Keywords: activated carbons; carbon capture; electrochemical applications; porous structures; surface chemistry